Medicinal Plant Leaf Extract From Sage and Lemon Verbena Promotes Intestinal Immunity and Barrier Function in Gilthead Seabream (Sparus aurata) - Salomón, Ricardo; Reyes-López, Felipe E.; Tort, Lluis; Firmino, Joana P.; Sarasquete, Carmen; Ortiz-Delgado, Juan B.; Quintela, José C.; Pinilla-Rosas, José M.; Vallejos-Vidal, Eva; Gisbert, Enric (Frontiers in Immunology, 2021)
The inclusion of a medicinal plant leaf extract (MPLE) from sage (Salvia officinalis) and lemon verbena (Lippia citriodora), rich in verbascoside and triterpenic compounds like ursolic acid, was evaluated in gilthead seabream (Sparus aurata) fed a low fishmeal-based diet (48% crude protein, 17% crude fat, 21.7 MJ kg-1) for 92 days. In particular, the study focused on the effect of these phytogenic compounds on the gut condition by analyzing the transcriptomic profiling (microarray analysis) and histological organization of the intestinal mucosa, as well as the histochemical properties of mucins secreted by goblet cells. A total number of 506 differentially expressed genes (285 up- and 221 down-regulated) were found when comparing the transcriptomic profiling of the intestine from fish fed the control and MPLE diets. The gut transcripteractome revealed an expression profile that favored biological mechanisms associated to the 1) immune system, particularly involving T cell activation and differentiation, 2) gut integrity (i.e., adherens and tight junctions) and cellular proliferation, and 3) cellular proteolytic pathways. The histological analysis showed that the MPLE dietary supplementation promoted an increase in the number of intestinal goblet cells and modified the composition of mucins’ glycoproteins produced by goblet cells, with an increase in the staining intensity of neutral mucins, as well as in mucins rich in carboxylated and weakly sulfated glycoconjugates, particularly those rich in sialic acid residues. The integration of transcriptomic and histological results showed that the evaluated MPLE from sage and lemon verbena is responsible for the maintenance of intestinal health, supporting gut homeostasis and increasing the integrity of the intestinal epithelium, which suggests that this phytogenic may be considered as a promising sustainable functional additive for aquafeeds.